The test : why our schools are obsessed with standardized testing-but you don't have to be - Kamenetz, Anya, 1980- (New York, NY : PublicAffairs, 2015)
"No sooner is a child walking and talking than the ABCs and 1-2-3s give way to the full-on alphabet soup: the ERBs, the OLSAT, the IQ, the NCLB for AYP, the IEP for ELLs, the CHAT and PDDST for ASD or LD and G&T or ADD and ADHD, the PSATs, then the ACTs and SATs-all designed to assess and monitor a child's readiness for education. In many public schools, students are spending up to 28% of instructional time on testing and test prep. Starting this year, the introduction of the Common Core State Standards Initiative in 45 states will bring an unprecedented level of new, more difficult, and longer mandatory tests to nearly every classroom in the nation up to five times a year-forcing our national testing obsession to a crisis point. Taxpayers are spending extravagant money on these tests-up to $1.4 billion per year-and excessive tests are stunting children's spirits, adding stress to family life, and slowly killing our country's future competitiveness. Yet even so, we still want our kids to score off the charts on every test they take, in elementary school and beyond. And there will be a lot of them. How do we preserve space for self-directed learning and development, while also asking our children to make the score and make a mark? This book is an exploration of that dilemma, and a strategy for how to solve it. The Test explores all sides of this problem-where these tests came from, why they're here to stay, and ultimately what you as a parent or teacher can do. It introduces a set of strategies borrowed from fields as diverse as games, neuroscience, social psychology, and ancient philosophy to help children do as well as they can on tests, and, just as important, how to use the experience of test-taking to do better in life. Like Paul Tough's bestseller How Children Succeed, it illuminates the emerging science of grit, curiosity and motivation, but takes a step further to explore innovations in education-emerging solutions to the over-testing crisis-that are not widely known but that you can adapt today, at home and at school. And it presents the stories of families of all kinds who are maneuvering within and beyond the existing educational system, playing and winning the testing game. You'll learn, for example, what Bill Gates, a strong public proponent of testing, does to stoke self-directed curiosity in his children, and how Mackenzie Bezos, wife of Amazon founder Jeff Bezos and mother of three, creates individualized learning experiences for each of her children. All parents want their children to be successful, and their schools to deliver true opportunities. Yet these goals are often as likely to result in stress and arguments as actual progress. The Test is a book to help us think about these problems, and ultimately, move our own children towards the future we want for them, from elementary to high school and beyond. "--
"In many public schools, students are spending up to 28 percent of instructional time on testing and test prep. Starting this year, the introduction of the Common Core State Standards Initiative in 45 states will bring an unprecedented level of new, more difficult, and longer mandatory tests to nearly every classroom in the nation up to five times a year--forcing our national testing obsession to a crisis point. Taxpayers are spending extravagant money on these tests--up to $1.4 billion per year--and excessive tests are stunting children's spirits, adding stress to family life, and slowly killing our country's future competitiveness. Yet even so, we still want our kids to score off the charts on every test they take, in elementary school and beyond. And there will be a lot of them. This book is an exploration of that dilemma, and a strategy for how to solve it"--
The problem. Ten arguments against testing ; The history of tests ; The politics of tests -- The solutions. Opting out ; The four teams ; Measuring what matters ; Playing and winning the testing game.
Includes bibliographical references and index.
Keywords: Education -- Standards -- United States; Educational tests and measurements -- United States; Education and state -- United States; Academic achievement -- United States